Dusk, night, dawn [large type] : on revival and courage - Lamott, Anne (Random House Large Print, 2021)
"In Anne Lamott's new book, she confronts the harsh truth that many of us grapple with every day: How can we recapture the confidence we once had in the world and in the future as we stumble through the dark times that seem increasingly bleak? As bad news piles up every day -- from climate crises to threats to democracy to daily assaults on civility -- how can we mere mortals cope?"--